Information and Communication Technologies in Education, Research, and Industrial Applications : 15th International Conference, ICTERI 2019, Kherson, Ukraine, June 12–15, 2019, Revised Selected Papers /: 15th International Conference, ICTERI 2019, Kherson, Ukraine, June 12–15, 2019, Revised Selected Papers. (2020) - Unknown
No abstract available